The Charter of Oregon City, Oregon, Together with the Ordinances and Rules of Order, at 259, Ordinance 209, § 2 (1898) - (:unkn) unknown (General Publisher, 1898)
Prohibited the carrying of any slingshot, billy, dirk, pistol, or “any concealed deadly weapon,” and the discharge of any firearm, air gun, sparrow gun, flipper, or bean shooter, unless in self-defense.
--
Keywords: CARRY